The hurricane - Washington, Denzel, 1954-; Jewison, Norman, 1926-2024; Hannah, John, 1962-; Unger, Deborah Kara; Schreiber, Liev; Carter, Rubin, 1937-; Chaiton, Sam, 1950-; Azoff Films (Firm); Universal Pictures (Firm); Beacon Pictures (Universal City, CA : Universal, 2000)
Rubin "Hurricane" Carter, in the prime of his boxing career, finds himself wrongfully convicted of murder. Sentenced to life in prison, Carter's published memoir, The sixteenth round, inspires a teenager from Brooklyn and three Canadian activists who believe in the truth, to join forces with Carter to prove his innocence. Special features include: "The making of The hurricane", feature commentary wtih director Norman Jewison, deleted scenes, theatrical trailer, production notes, cast and filmmakers, and DVD-ROM features.
Based on: The 16th round / by Rubin Carter, and: Lazarus and the hurricane / by Sam Chaiton and Terry Swinton.
Originally released as motion picture in 1999.
Special features: Spotlight on location: the making of The hurricane ; feature commentary with director Norman Jewison ; deleted scenes with special introducation by the director ; theatrical trailer ; production notes ; cast and filmmakers ; DVD-ROM features.
Director of photography, Roger Deakins; editor, Stephen Rivkin; music, Christopher Young.
Starring: Denzel Washington, John Hannah, Deborah Kara Unger, Liev Schreiber.
MPAA rating: R.
Keywords: Carter, Rubin, -- 1937- -- Drama; Judicial error -- United States -- Drama; African American boxers -- Drama; Trials (Murder) -- Drama; Video (DVD); Feature films; Video recordings for the hearing impaired; French language materials -- Bilingual